AB023. Penile rehabilitation with phosphodiesterase type 5 inhibitors in men after nerve-sparing radical prostatectomy - Jiann, Bang-Ping (Transl Androl Urol, 2016)
Post-radical prostatectomy (RP) erectile dysfunction (ED) remains a challenge for the urologist. Despite the improvements in surgical technique, ED occurs between 20% and 90% in patients treated with bilateral nerve-sparing RP. Patient factors, cancer selection, type of surgery, surgical techniques, and surgeon factors represent the key significant contributors to erectile function recovery. The aim of a penile rehabilitation program is to preserve the functional smooth-muscle content of the corpus cavernosum during the neuropraxia period. Phosphodiesterase type 5 (PDE5) inhibitors are commonly used in rehabilitation programs. In animal models, such an approach could promote erectile function recovery, improve smooth muscle-to-collagen penile ration, reduce penile apoptotic index, preserve penile endothelial function and promote neuroprotection during nerve damage. Despite the strong basic science support from animal studies, discordant results have been reached in humans. The previous randomized trials comparing chronic versus on-demand PDE-5 inhibitors use after RP may be affected by improper patients’ selection in that only men at low risk of postoperative ED were included. These patients would recover erectile function regardless of the type of PDE5 inhibitor administration because of their excellent baseline profile. Prospective, randomized trials have shown a significant benefit of daily PDE5-I administration as compared with placebo in terms of postoperative EF recovery. Patients with intermediate risk of ED after surgery are the best candidates for daily treatment with PDE5 inhibitor after bilateral nerve-sparing RP. The maximal effect of penile rehabilitation may be found in those men with a certain (but not high) degree of systemic and erectile impairment preoperatively. In conclusion, penile rehabilitation could achieve faster and better natural erectile function after RP and should be started as early as possible. Chronic use of PDE5-I may confer the maximal gain as compared to the on-demand administration schedule. Attention should be pained to the observation that rehabilitation protocols are beneficial even in men with spontaneous erections postoperatively because further improvement in such patients was reported.